1-7x-3x=-9

Simple and best practice solution for 1-7x-3x=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-7x-3x=-9 equation:



1-7x-3x=-9
We move all terms to the left:
1-7x-3x-(-9)=0
We add all the numbers together, and all the variables
-10x+10=0
We move all terms containing x to the left, all other terms to the right
-10x=-10
x=-10/-10
x=1

See similar equations:

| 600+0.03x=2400 | | 2y-5=32 | | 10.50p+14=15(p-5) | | -5(v+3)+2v+7=8v+9 | | 3(x-2)+11=5(x-3)+5 | | y=4^2+10 | | m+(m-)=7 | | v/7-5=-3 | | 14x-3+(-4x)=5x+17 | | y=1/5-5-9 | | 5(X+3)=18x+2 | | 6y+15=5y+21 | | 9(x–2)=3x+3 | | 4(r+20)=5(2r+4) | | 4(2x+7)=-43+31 | | 5x+6=3(x+2)+2x | | 1/6x1/9x=1(18) | | 4(x+10)=4-5x | | 7aX3=21 | | 2+15x=4+5x | | y=6^2-6 | | 6=x/2-5 | | 7-5y=-4y | | -7(v-2)+4=18-7v | | -u+285=103 | | 5(2x+4)-8=10x-18+2x | | 4x-28x=-33 | | –10+5k=6k | | (18+4)+m+m((5-3)=22 | | -8r+18=-30 | | 9w-3w-12=48 | | 0.75p+0.5=2.75 |

Equations solver categories